Inflammation, dysregulated iron metabolism, and cardiovascular disease - Rosenblum, Shaina L. (Frontiers in Aging, 2023)
Iron is an essential trace element associated with both pathologic deficiency and toxic overload. Thus, systemic and cell iron metabolism are highly controlled processes regulated by protein expression and localization, as well as turnover through the action of cytokines and iron status. Iron metabolism in the heart is challenging because both iron overload and deficiency are associated with cardiac disease. Also associated with cardiovascular disease is inflammation, as many cardiac diseases are caused by or include an inflammatory component. In addition, iron metabolism and inflammation are closely linked. Hepcidin, the master regulator of systemic iron metabolism, is induced by the cytokine IL-6 and as such is among the acute phase proteins secreted by the liver as part of the inflammatory response. In an inflammatory state, systemic iron homeostasis is dysregulated, commonly resulting in hypoferremia, or low serum iron. Less well characterized is cardiac iron metabolism in general, and even less is known about how inflammation impacts heart iron handling. This review highlights what is known with respect to iron metabolism in the heart, primarily focusing on studies in heart endothelial cells, cardiomyocytes, pericytes, and fibroblasts. Expression of iron metabolism-related proteins and processes of iron uptake and efflux in these cell types are outlined. Evidence for the strong co-morbid relationship between inflammation and cardiac disease is also reviewed. Known connections between inflammatory processes and iron metabolism in the heart are discussed with the goal of linking inflammation and iron metabolism in this tissue, a connection that has been relatively under-appreciated as a component of heart function in the inflammatory state. Therapeutic options connecting inflammation and iron balance are emphasized, with the main goal of this review being to bring attention to alterations in iron balance as a component of inflammatory diseases of the cardiovascular system.